Characterization of the Components of Formative Research in the Contemporary University in Latin America - Corona Meza, Wilfrido (2023)
The objective of this article is based on the bibliographical review through documentary analysis, with emphasis on the heuristic, hermeneutic and holistic phases of the components that shaped the formative research operationalization in the current Latin America university with the purpose of characterizing and strengthening the teaching-learning processes carried out in this educative experience. This paper focused on four dimensions of analysis named: formative research epistemology referring to the conception and implementation by educational actors; students’ development of investigative skills during their academic formation; teaching practice of research project professors and/or tutors, as well as institutional strategies used to promote scientific culture through academic activities and university policies. It presents and discusses different theoretical contributions, academic proposals and institutional strategies which have gradually helped universities and their educative actors to reach the objectives set out in the institutional policies, both national and international, regarding research. It seeks to obtain the consolidation of professionals’ integral formation which promotes the construction of better societies from the study areas that form the higher education system. As part of the results, it was found that Latin American universities conceive and implement formative research in a similar form looking for its consolidation. However, within the conclusions, it can be observed that there are educational processes related to formative research which need to be strengthened such as: the level of development of the students’ investigative skills, the formation in research and teaching of the professors, as well as the diversification of academic activities and the revision of institutional policies for their adaptation to the current needs of formative research.